Analysis of applied governance and impact on the financial Sector popular and solidary (SFPS) of the metropolitan district of Quito (DMQ) in the years 2014 - 2016 - Catota Díaz, Eva Marina; Román Vásquez, José Luis (SATHIRI, 2021)
The investigation aims to analyze applied governance and its impact on the entities of the Popular and Solidarity Financial Sector (PSFS) of Segment One of the (Quito Municipal District) QMD during the period from 2014 to 2016. Its importance lies in the way of managing companies which is more cooperative and participatory by involving public and private participants to achieve business objectives. The theoretical framework helps to support the work carried out and the researcher to deepen the scope of governance. It was planned an analytical methodology through a descriptive affect in which 8 entities that belong to Segment One of the PSFS of the MDQ were identified. These ones were applied a primary investigation through the collection of financial reports to know the economic situation during the investigation lasted. In the same way, a poll was applied to a total of 80 functionaries from these financial institutions according to the governance criteria, which allowed to detect the running of an effective management. As a result, it is seen strengthened by the constant evaluation of the activities in order to fulfill the institutional objectives. Finally, a governance model, is proposed. It is based on low investigation scores and focused on improving processes in the PSFS Segment One, which ones are: personal criteria and strategic management.